Evaluating the Preparedness of Healthcare Providers for Prone Position CPR Across Jordan's Healthcare Sectors: A Descriptive Cross‐Sectional Study - Ahmad Al Hroub; Sami Al‐Yatim; Majeda Al‐Ruzzieh (Health Science Reports)
ABSTRACT Background and Aims Healthcare providers may need to initiate cardiopulmonary resuscitation (CPR) while patients are in the prone position. Healthcare providers (HCPs) must possess the necessary knowledge, skills, and experience to perform cardiopulmonary resuscitation in the prone position (PPCPR) confidently. This study aimed to assess HCPs' preparedness to perform cardiopulmonary resuscitation in the prone position at specialized units in Jordan's healthcare sectors. Methods In eight tertiary hospitals, a descriptive cross‐sectional survey was carried out. An online questionnaire was conducted among 332 HCPs who were employed in the operating room, intensive care units, or interventional procedure rooms. Results The majority of HCPs (73%) exhibited poor preparedness, with only 25% showing excellent preparedness, and 2% displayed an average level of preparedness. The average preparedness score was 37.14 (SD = 38.840), indicating significant variability. A lack of targeted training was associated with lower preparedness levels. Notably, HCPs with Advanced Cardiac Life Support (ACLS) training showed significantly higher preparedness. Conclusion The HCPs in Jordan are poorly prepared to perform PPCPR whenever required. However, the study findings represent a significant step towards improving HCPs' preparedness to perform PPCPR. They serve as a baseline assessment and highlight the gaps in HCPs' readiness, which helps their organizations to develop and implement targeted training strategies and interventions. Incorporating this training into hospital orientation, training programs, and clinical guidelines is vitally important to enhance HCPs' capabilities for better outcomes.